Methylphenidate improves motor functions in children diagnosed with Hyperkinetic Disorder - Stray, Liv Larsen (BioMed Central, 2009)
BACKGROUND: A previous study showed that a high percentage of children diagnosed with Hyperkinetic Disorder (HKD) displayed a consistent pattern of motor function problems. The purpose of this study was to investigate the effect of methylphenidate (MPH) on such motor performance in children with HKD METHODS: 25 drug-naïve boys, aged 8–12 yr with a HKD-F90.0 diagnosis, were randomly assigned into two groups within a double blind cross-over design, and tested with a motor assessment instrument, during MPH and placebo conditions. RESULTS: The percentage of MFNU scores in the sample indicating 'severe motor problems' ranged from 44–84%, typically over 60%. Highly significant improvements in motor performance were observed with MPH compared to baseline ratings on all the 17 subtests of the MFNU 1–2 hr after administration of MPH. There were no significant placebo effects. The motor improvement was consistent with improvement of clinical symptoms. CONCLUSION: The study confirmed our prior clinical observations showing that children with ADHD typically demonstrate marked improvements of motor functions after a single dose of 10 mg MPH. The most pronounced positive MPH response was seen in subtests measuring either neuromotor inhibition, or heightened muscular tone in the gross movement muscles involved in maintaining the alignment and balance of the body. Introduction of MPH generally led to improved balance and a generally more coordinated and controlled body movement.